2013
DOI: 10.1098/rspb.2013.0584
|View full text |Cite
|
Sign up to set email alerts
|

More than a colour change: insect melanism, disease resistance and fecundity

Abstract: A 'dark morph' melanic strain of the greater wax moth, Galleria mellonella, was studied for its atypical, heightened resistance to infection with the entomopathogenic fungus, Beauveria bassiana. We show that these insects exhibit multiple intraspecific immunity and physiological traits that distinguish them from a non-melanic, fungus-susceptible morph. The melanic and non-melanic morphs were geographical variants that had evolved different, independent defence strategies. Melanic morphs exhibit a thickened cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
137
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(157 citation statements)
references
References 42 publications
(70 reference statements)
10
137
0
3
Order By: Relevance
“…Some studies reported a possible positive correlation between melanisation, PO activity, and tolerance to parasites and pathogens such as B. bassiana and M. anisopliae [59,60]. In our electron microscopy studies of the head region, we found that infection of M. brunneum blastospores triggers a melanisation response by Cx.…”
Section: Discussionsupporting
confidence: 60%
“…Some studies reported a possible positive correlation between melanisation, PO activity, and tolerance to parasites and pathogens such as B. bassiana and M. anisopliae [59,60]. In our electron microscopy studies of the head region, we found that infection of M. brunneum blastospores triggers a melanisation response by Cx.…”
Section: Discussionsupporting
confidence: 60%
“…The initial constitutive response may be the immune response that is the most important for survival (e.g. Lochmiller and Deerenberg, 2000;Dubovskiy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Insect melanin New Journal of Science 7 is not just and ornament. In birds and insects, it is used the term "melanism," which is a costly mechanism enabling the protective trait in natural selection and it constitutes more than just a color change in the polymorphisms of a number of insect species [88,89]. Insect melanogenesis is also considered as a process related to the insect innate immunity [90,91] and insect hemostasis [92].…”
Section: Animal Melaninsmentioning
confidence: 99%